A retrospective study of the epidemiology and clinical manifestation of invasive aspergillosis in a major tertiary care hospital in Bahrain - Jameela Alsalman; Thuraya Zaid; Mohamed Makhlooq; Maysa Madan; Zahra Mohamed; Amani Alarayedh; Aysha Ghareeb; Nermin Kamal (Elsevier, 2017)
Summary: Limited data are available on the epidemiology, clinical manifestations and outcomes of patients with invasive aspergillosis in Bahrain. This study was conducted retrospectively to determine the epidemiology of invasive aspergillosis and its risk factors, clinical presentation, underlying conditions, and outcomes over the past five years in a major hospital.The medical records of patients with positive Aspergillus cultures admitted to a major tertiary care hospital in Bahrain during 2009-2013 were reviewed. Cases were classified according to (1) the European Organization for the Research and Treatment of Cancer/Mycoses Study Group (MSG) criteria (proven, probable, possible IA or not classifiable) and (2) "validated" criteria to distinguish Aspergillus colonization from IA (putative or proven IA). Demographic, microbiologic and diagnostic data were collected, and outcomes were recorded.A total of 60 patients were included, of whom 44 were colonized (73.3%), and 16 had probable IA (26.7%); no proven or possible IA cases were identified according to the EORTC/Mycoses Study Group (MSG) criteria. In comparison, with the alternative "validated" criteria, 32 were colonized (53.3%), 28 had putative IA (46.7%), and none had proven IA (0%). The lung was the most common site of infection, and Aspergillus fumigatus was the most commonly isolated species (53%). Mortality was 25% among colonized patients, 44% in probable cases and 32% in those with putative IA. All patients were immunocompromised or had one or more predisposing factors. Independent risk factors for death among patients with IA included older age, history of mechanical ventilation, renal replacement therapy and higher sequential organ failure assessment scores at diagnosis. Keywords: Aspergillus, Epidemiology, Treatment, Mortality, Infection